Evaluation of the Isomerization of α-Pinene Epoxide to Campholenic Aldehyde Using a Catalyst Obtained from Orange Peels (Citrus sinensis) (2023)
Orange peels (Citrus sinensis) are an abundant lignocellulosic residue that can be used as a carbon source to obtain solids with catalytic potential in the transformation of terpenes and their oxides into value-added products. This research seeks to evaluate the isomerization of α-pinene epoxide to campholenic aldehyde using a catalyst obtained from orange peels. The material OAC-Zn was obtained by activation of orange peel with ZnSO4.7H2O followed by thermal treatment at 500 °C; an additional solid was obtained from orange peel by pyrolysis at 500 °C (OC-500). XRD revealed the presence of ZnO and ZnS in OAC-Zn; TGA analysis indicated thermal stability in OAC-Zn and OC-500 materials; SEM images showed porous surfaces of different morphology, and the presence of microporosity in OC-500 and mesoporosity in the OAC-Zn that was confirmed by physical nitrogen adsorption. The elements C, O, Zn and S were identified in OAC-Zn by EDX analysis. The results of TPD-NH3 showed that the solids contained medium and weak acidity. Campholenic aldehyde was synthesized with a 96 % selectivity over the material OAC-Zn.